Development and Management of Tourism Village with Creative Economy Concept Towards Prosperity in Increasing Income - Zakiyah, Rahayu Dewi; Winata, A Yahya Surya (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to determine how much influence the development and management of the economy in terms of the concept of Creative Economy towards Prosperity in Increasing Revenue applied to tourist villages. Economic development is supported by good management, one of which is by utilizing the Creative Economy using a digitalization technology system, and telecommunications will maximize performance so that it can improve the welfare of the people in tourist villages. This type of research is qualitative research using primary data. The data collection techniques used are observation, interview, and documentation methods. The results showed that with the concept of creative economy can improve the welfare and income of the tourist village community by utilizing current digitalization, the development of the current era is a demand for people to be able to take advantage of technology.